The Effect of Submaximal Exercise on Cutaneous Blood Flow, Thermoregulation and Recovery Hemodynamics Following Endurance Exercise - Nejka Potočnik (Southeastern European Medical Journal, 2022)
Aim. There are numerous reports of attenuation of cutaneous blood flow (CBF) during the recovery period after a single bout of exercise, but no one has investigated the CBF response to consecutive short-lasting aerobic exercise (SLAE) sessions following exhaustive endurance exercise (EEE) on daily basis, although this is a commonly used training regime in recreational athletes and could cause a cumulative increase in CBF that may be important for wound healing. This study examined the effects of EEE on forearm skin blood flow (LDF), cutaneous vascular conductance (CVC), and mean arterial pressure (MAP) in response to SLAE sessions performed for 7 days after EEE, as well as the correlation between cutaneous blood flow and indices associated with heart rate (HR) to examine the role of thermoregulation in post-exercise HR regulation.